2017
DOI: 10.1002/mop.30490
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐angle and polarization‐independent broadband microwave metamaterial absorber

Abstract: We present a broadband metamaterial absorber (MA) in the microwave frequency regime by utilizing a periodic array of metallic‐dielectric multilayered conical frustums. The absorption performance of the proposed MA is simulated and analyzed in details by using the finite‐difference time domain method. The absorption efficiencies greater than 90% can be achieved while maintaining with large incidence angles up to 600. Furthermore, the perfect polarization independence is also obtained due to its rotational symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some approaches have been developed for bandwidth enhancement 28 . Among those common ones, one uses the two-dimensional patterns of blending various unit cells of PA peak 24 , while the other utilizes the stacking multilayer of metallic and dielectric 58 . However, these approaches exhibit some disadvantages such as limitation of absorption bandwidth and sophistication of the fabrication process, thus prevent for real application of these MA devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some approaches have been developed for bandwidth enhancement 28 . Among those common ones, one uses the two-dimensional patterns of blending various unit cells of PA peak 24 , while the other utilizes the stacking multilayer of metallic and dielectric 58 . However, these approaches exhibit some disadvantages such as limitation of absorption bandwidth and sophistication of the fabrication process, thus prevent for real application of these MA devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the first method, the absorption band is not wide enough due to their resonance features 7 . Meanwhile, in the second one, the bandwidth of MA can be controlled via increasing the number layer of metal/dielectric 5 . However, the multilayer structure remains truly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure exhibits incident angle insensitivity below 40° due to its low-level symmetrical structures. To examine the influence of incidence angle on absorption properties of the broadband absorber with multilayered symmetrical structures, Hoa et al reported the broadband microwave MA based on a periodic arrangement of metallic/dielectric multilayered conical frustums [88]. The MA exhibits a perfect absorption with a wide angle of tolerance and polarization insensitivity due to its rotational symmetrical structure.…”
Section: Issues Of Polarization and Incidence Anglementioning
confidence: 99%
“…The absorption peaks can be tuned by optimizing the shaped metallic grating structure located at the top of the MA. Recently, many efforts have been studied to widen the absorption bandwidth by using multi-shaped metallic configurations stacking of dielectric-meta layers [18,19], hole-arrays working as resonators [20], the shaped rectangular grating [21], shaped L grating [22,23], cylinder array [24], epsilon-near-zero (ENZ) materials [25,26], nanoporous materials that exhibit high efficiency in terms of broadband absorption, as well as their high applicability in sensors and easily fabricable devices [27][28][29][30]. However, these MA structures still have many disadvantages such as narrow absorption bandwidth, and polarization sensitivity due to the asymmetry structures having a low order of rotational symmetry, whereas many practical applications require the polarization-insensitive feature.…”
Section: Introductionmentioning
confidence: 99%